2013
DOI: 10.1177/1040638713508400
|View full text |Cite
|
Sign up to set email alerts
|

Availability of a fetal goat tongue cell line ZZ-R 127 for isolation of Foot-and-mouth disease virus (FMDV) from clinical samples collected from animals experimentally infected with FMDV

Abstract: Abstract. The availability of the fetal goat tongue cell line ZZ-R 127 for the isolation of Foot-and-mouth disease virus (FMDV) has not been evaluated using clinical samples other than epithelial suspensions. Therefore, in the current study, the availability of ZZ-R 127 cells for the isolation of FMDV was evaluated using clinical samples (e.g., sera, nasal swabs, saliva, feces, and oropharyngeal fluids) collected from animals experimentally infected with an FMDV isolate. Virus isolation rates for the ZZ-R 127 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Fetal porcine kidney (LFBK-α V β 6 ) cells, which have been engineered to express bovine α V β 6 integrin, a principal cellular receptor of FMDV, and fetal goat tongue cells (ZZ-R 127) are two continuous cell lines that are highly sensitive to FMDV (10)(11)(12). A number of studies have utilized the LFBK-α V β 6 and ZZ-R 127 cell lines for the isolation of FMDV from different clinical samples (13)(14)(15)(16)(17)(18)(19)(20). In previous studies, the ZZ-R 127 cell line provided similar sensitivity to FMDV as primary BTY cells (10) and LFBK-α V β 6 cells (21), however to our knowledge the LFBK-α V β 6 cell line has not been compared to BTY cells.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal porcine kidney (LFBK-α V β 6 ) cells, which have been engineered to express bovine α V β 6 integrin, a principal cellular receptor of FMDV, and fetal goat tongue cells (ZZ-R 127) are two continuous cell lines that are highly sensitive to FMDV (10)(11)(12). A number of studies have utilized the LFBK-α V β 6 and ZZ-R 127 cell lines for the isolation of FMDV from different clinical samples (13)(14)(15)(16)(17)(18)(19)(20). In previous studies, the ZZ-R 127 cell line provided similar sensitivity to FMDV as primary BTY cells (10) and LFBK-α V β 6 cells (21), however to our knowledge the LFBK-α V β 6 cell line has not been compared to BTY cells.…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility of ZZ-R 127 cells to virus isolation has already been evaluated using clinical samples collected from animals infected experimentally with a FMDV strain. 5 However, the susceptibility of the LFBK-α v β 6 cells to virus isolation has not been evaluated using clinical samples other than epithelial materials, to our knowledge. Therefore, an evaluation of the susceptibility of LFBK-α v β 6 cells to virus isolation with sample types other than epithelium was the first objective of this study.…”
mentioning
confidence: 99%
“…The suitability of ZZ-R 127 cells for FMDV isolation not only from epithelial suspensions but also from other clinical samples such as sera, saliva, nasal swabs, and oropharyngeal fluids has already been confirmed. 5 However, the suitability of LFBK-α v β 6 cells for virus isolation from clinical samples other than epithelial suspensions has not been evaluated, to our knowledge. In the current study, although slight difference in the virus isolation rates was observed between the ZZ-R 127 and LFBK-α v β 6 cell lines across the animal species from which the clinical samples used in this study were collected, viruses were isolated at almost the same rate from samples by the ZZ-R 127 and the LFBK-α v β 6 cell lines.…”
mentioning
confidence: 99%
“…This makes these cells inapt for rapid diagnostics because fresh cells from thyroid tissue have to be available each time for virus isolation, which is expensive, time consuming and laborious. A study by Brehm et al (2009) showed that a goat fetal tongue cell line (ZZR-127) has sensitivity equivalent to BTY cells and there are other studies that have been performed using this cell line that also support Brehm et al's findings (Fukai et al, 2013(Fukai et al, , 2015. Another cell line with reputable FMDV sensitivity is the fetal porcine kidney cell line (LFBK-α V β 6 ).…”
Section: Introductionmentioning
confidence: 82%